Nuclear Progesterone Receptors Are Up-Regulated by Estrogens in Neurons and Radial Glial Progenitors in the Brain of Zebrafish - Diotel, Nicolas; Servili, Arianna; Gueguen, Marie-Madeleine; Mironov, Svetlana; Pellegrini, Elisabeth; Vaillant, Colette; Zhu, Yong; Kah, Olivier; Anglade, Isabelle (My University, 2011)
Abstract In rodents, there is increasing evidence that nuclear progesterone receptors are transiently expressed in many regions of the developing brain, notably outside the hypothalamus. This suggests that progesterone and/or its metabolites could be involved in functions not related to reproduction, particularly in neurodevelopment. In this context, the adult fish brain is of particular interest, as it exhibits constant growth and high neurogenic activity that is supported by radial glia progenitors. However, although synthesis of neuroprogestagens has been documented recently in the brain of zebrafish, information on the presence of progesterone receptors is very limited. In zebrafish, a single nuclear progesterone receptor (pgr) has been cloned and characterized. Here, we demonstrate that this pgr is widely distributed in all regions of the zebrafish brain. Interestingly, we show that Pgr is strongly expressed in radial glial cells and more weakly in neurons. Finally, we present evidence, based on quantitative PCR and immunohistochemistry, that nuclear progesterone receptor mRNA and proteins are upregulated by estrogens in the brain of adult zebrafish. These data document for the first time the finding that radial glial cells are preferential targets for peripheral progestagens and/or neuroprogestagens. Given the crucial roles of radial glial cells in adult neurogenesis, the potential effects of progestagens on their activity and the fate of daughter cells require thorough investigation.